2017
DOI: 10.1111/cas.13122
|View full text |Cite
|
Sign up to set email alerts
|

Antizyme inhibitor 1: a potential carcinogenic molecule

Abstract: Polyamines are multivalent and organic cations essential for cellular growth, proliferation, differentiation, and apoptosis. Increased levels of polyamines are closely associated with numerous forms of cancer. An autoregulatory circuit composed of ornithine decarboxylase (ODC), antizyme (AZ) and antizyme inhibitor (AZI) govern the intracellular level of polyamines. Antizyme binds with ODC to inhibit ODC activity and to promote the ubiquitin‐independent degradation of ODC. Antizyme inhibitor binds to AZ with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
(105 reference statements)
1
26
0
Order By: Relevance
“…AHR is a direct transcriptional activator of ODC1 and AZIN1. ODC1 and AZIN1 have been shown to have protumorigenic functions (12)(13)(14), and anti-polyamine agents have long been under consideration as chemotherapeutic agents, although none is currently in clinical use (2). Thus, a therapeutic strategy aimed at the simultaneous inhibition of ODC1 and AZIN1 may prove beneficial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AHR is a direct transcriptional activator of ODC1 and AZIN1. ODC1 and AZIN1 have been shown to have protumorigenic functions (12)(13)(14), and anti-polyamine agents have long been under consideration as chemotherapeutic agents, although none is currently in clinical use (2). Thus, a therapeutic strategy aimed at the simultaneous inhibition of ODC1 and AZIN1 may prove beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of the transcription factors MYC (8)(9)(10) and SP1 (11), little is known about the transcriptional regulation of polyamine biosynthesis. Importantly, although both ODC1 and AZIN1 have been shown to have protumorigenic functions (12)(13)(14) and anti-polyamine agents have been under consideration as chemotherapy, none is currently in clinical use (2).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, work performed in cell culture models showed that the Aurora A kinase interacting protein 1 (AURKAIP1) enhances the binding of Antizyme1 (AZ1) on AURKA [62][63][64]. AZ1 is an enzyme belonging to the polyamine biosynthesis pathway, and it is known to regulate ubiquitin-independent protein degradation programs [65]. According to its enzymatic function, AZ1 promotes the ubiquitin-independent, but proteasome-dependent degradation of AURKA after mitotic exit [63,64].…”
Section: Emerging Roles Of Aurka Outside Mitosis: Novel Subcellular Lmentioning
confidence: 99%
“…One example is ADAR-1 editing of the Antizyme Inhibitor 1 (AZIN1), which leads to a serine-to-glycine substitution at residue 367 [41]. AZIN1 is an inactive homolog of ornithine decarboxylase (ODC) that competitively binds to antizymes [42]. ADAR-1 editing increases AZIN1 affinity to antizyme, leading to a decrease in ODC antizyme-mediated degradation and promoting polyamines biosynthesis, with consequent cell proliferation and a more aggressive behavior in hepatocellular carcinoma cells [41].…”
Section: Mrna Processingmentioning
confidence: 99%